Managing Volunteer Programs: Educational Strategies for Adult Learners - Marilyn K. Lesmeister; Shannon Washburn; David Jones (EDIS)
FCS-9241, a 5-page fact sheet by Marilyn K. Lesmeister, Shannon Washburn, and David Jones, describes the characteristics of adult learners and barriers to adult learning, and describes three strategies to engage adult learners with subject matter and one another: Think/Pair/Share, round robin discussion, and role-play. Includes references. Published by the UF Department of Family Youth and Community Sciences, May 2006.